Combined Effect Of NozzleDispersion Device On Spray Pattern Uniformity For Low Pressure Sprinklers - Issaka, Zakaria; Fordjour, Alexander; Adetunji Ibrahim, Ajani (European Scientific Journal, ESJ, 2020)
An impact sprinkler with a newly designed nozzle-dispersion device and R33 sprinkler were introduced in this study. Comparative experiments and analyses on uniformity patterns of impinging water jet from both sprinklers were investigated by using high-speed photographic technique to visualize the spray. A mathematical model of the spray was developed and applied in MatLab to determine the spray angles at different axial distances. Results showed that the impact sprinkler with the nozzledispersion device combination gave the largest spray range of 12.6% larger than the R33 sprinkler. Combined effect of the nozzle-dispersion device for the impact sprinkler had a strong effect on the spray angle which increased with increasing pressure. Spray characteristics for the impact sprinkler were similar to those produced by the R33 sprinkler. The number of droplets increased with increasing spray angle due to early breakup of the jet, which is beneficial for greater water dispersion and uniformity. It was found that a low working pressure of 150 kPa leads to lower degree of nonuniformities for the sprinklers, and the variation coefficient were less than 10%. Obtained mathematical models of the changes in the variation coefficient was dependent upon working pressure and can be a good basis for easy management of the parameters necessary for the uniform spray distribution. Hence, the impact sprinkler with the nozzle-dispersion device can offer superior advantage of a larger spray range for better overlap and disperse more droplets for better Uniformity under low pressure conditions.